Evaluation of a summation formula associated with Gamma function and involving Gauss Theorem (Global Journal of Science Frontier Research, 2012)
The aim of this paper is to evaluate a summation formula based on half argument allied with Hypergeometric function and involving recurrence relation and Gauss summation theorem.
Keywords: Contiguous relation; Gauss second summation theorem; Re-currence relation